MENINGKATKAN KETERAMPILAN MEMBACA BAHASA ARAB MELALUI MODEL QUANTUM TEACHING DI MAN 3 PADANG PANJANG - Susanti, Yuli (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
This study aims to describe the second semester of first grade students’ achievement in learning reading of Arabic language at MAN 3 Padang Panjang by using quantum teaching model. This is a classroom action research using Kemmis and Burns model. The result shows that implementing quantum teaching in Arabic learning can improve students’ ability in reading. The improvement is proved by reading scores obtained by students in every cycle. The mean score at cycle I is 69.96, at cycle II is 74.42, and at cycle III is 83.91. It means that there is an improvement of students’ motivation at every cycle. The percentage of students’ motivation at cycle I is 63.75%, at cycle II is 77%, and at cycle III is 84.9%. The implementation of quantum teaching model has increased which can be seen by the improvement of students’ achievement in every cycle.